Digital Media Strategies of Luxury Brands - Zeybek, Işıl; Ekin, Volkan (2012)
Institutions that provide products and services and that show activity in all areas, not only are agents of change but also lead the race in novelties under the wind of change in a rapidly digitalizing world. In this sense, digital spaces are “new channels” where access to products and services is faster, thus facilitating the lives of individuals. These digital spaces are used especially by brand owners, where, though their specific strategies of digital marketing, they are able to reach consumers. This study will concentrate on brands that connote meanings of “luxury” and see what kind strategies they use in digital spaces. These strategies no doubt differ from other brands, which use more “daily” and “common” methods of marketing. Marketers need to orient consumers in a particular manner in order to them to purchase luxury items online. In this context, this study will look at the relationship between luxury brands and their target audience in the internet based new economic platform, and how products associated with “luxury” are focused on “value” on the internet. An example will be taken and will be analyzed with a semiological method of analysis, where the influence of the strategies of luxury brands on the attitude of consumers will be evaluated.
Keywords: Luxury; Digital Channels; Brand; Strategy